ANALISIS SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN TERPUSAT DALAM OPTIMALISASI PELAYANAN PUBLIK DI KABUPATEN SERANG - Hendra Purnama, Dite; Bambang Nurcahya, Said (Jurnal Teknologi Komputer dan Informatika, 2023)
The centralized population administration information system used for public services is currently used to ensure the arrangement of population administration and civil records in Serang Regency in collaboration with the Directorate General of Population and Civil Registration, with Centralized SIAK the community will receive the same service standards in each region. Because, all population administration services are provided in Dukcapil services in the regions can be controlled by all parties. Both the government and the population. In conducting this research, the author immediately created a Discussion Group Forum involving 29 sub-districts and the Population Service as the Leading sector using descriptive analysis, this analysis method is the analysis used by the majority of analysts, to display statistics through mathematical calculations. Its function is to understand the distribution of sample or population data. So the data will be easy to understand and more informative. The discussion of field results regarding the centralized SIAK application analysis which has been carried out over a period of 10 months in 2023 can be used as an evaluation of the performance of the Serang Regency Regional Government to further increase regional competitiveness in attracting investment and building for community prosperity as well as providing transparency of economic and development information. integrated through information technology.